(untitled) (Journal of the College of Basic Education, 2023)
This study aims at (the effect of participatory learning in developing the creative writing skills of the fourth literary grade students). To achieve this, the researcher selected a sample of (60) female students from the fourth literary grade in Zainab Al-Kubra Preparatory School for Girls in Diyala Education, Al-Asri neighborhood, with (30) students for the experimental group and (30) students for the control group. The researcher studied the experimental group by adopting participatory learning strategies and the group The control is the traditional method. The researcher rewarded the female students of the two research groups in the variables of chronological age calculated in months, educational attainment of parents, intelligence test, and language ability test. The researcher controlled extraneous variables that may affect this type of experimental design. After the researcher identified the scientific material, which included (8) topics from the Arabic language book, which is to be taught to female students in the fourth literary grade for the academic year 2022-2023. The researcher formulated the behavioral goals of the teaching plans for the subjects, and the final number reached (115) behavioral goals, and the researcher prepared model teaching plans for each of the topics specified for the experiment, and in order to measure the creative writing of the students of the two research groups, the researcher prepared a creative writing test. After applying the research tool and analyzing the results obtained by the researcher statistically, the researcher concluded that teaching by adopting participatory learning in creative writing skills is better for fourth grade literary students compared to the usual method. She recommended the need to adopt participatory learning in the creative writing skills of the fourth grade literary students, and the researcher suggested subsequent studies similar to the current study in the rest of the branches of the Arabic language